Nano-drug delivery systems (NDDS) in metabolic dysfunction-associated steatotic liver disease (MASLD): current status, prospects and challenges - Yang, Ying; Wang, Xiaojing (Frontiers in Pharmacology, 2024)
About one-third of the global population suffers from metabolic dysfunction-associated steatotic liver disease (MASLD), but specific treatments for MASLD have long been lacking, primarily due to the unclear etiology of the disease. In addition to lifestyle modifications and weight loss surgery, pharmacotherapy is the most common treatment among MASLD patients, and these drugs typically target the pathogenic factors of MASLD. However, bioavailability, efficacy, and side effects all limit the maximum therapeutic potential of the drugs. With the development of nanomedicine, recent years have seen attempts to combine MASLD pharmacotherapy with nanomaterials, such as liposomes, polymer nanoparticles, micelles, and cocrystals, which effectively improves the water solubility and targeting of the drugs, thereby enhancing therapeutic efficacy and reducing toxic side effects, offering new perspectives and futures for the treatment of MASLD.